HEDONIC VALUE AND UTILITARIAN VALUE IN FOOD TRUCK BUSINESS: A QUALITATIVE PERSPECTIVE - Firmansyah Firmansyah; Tona Aurora Lubis; Maryati Ningsih (Management Department, Faculty of Economics and Business, Universitas Jambi, 2022)
The culinary industry grows and develops because of the phenomenon of the growth and development of the street food business. One of the developments in the way food and beverage is served is selling via trucks or â€œmobile restaurantsâ€, better known as Food trucks. The growth of the Food Truck business shows significant growth due to the increasing behavior of people's consumption of food and beverages offered by the Food Truck media. This research is qualitative research. This study uses respondents who have made purchase transactions at the food truck business in Jambi City. At this qualitative stage, the themes and sub-themes of the research were obtained. The hedonic value theme has sub-themes in the form of fun, curiosity, entertainment, a variety of product flavors, hygienic factors, creativity, and innovation, as well as attracting attention. The utilitarian value theme has sub-themes in the form of time efficiency, affordable prices, practicality, and strategic location. While on the purchasing decision theme, there are sub-themes in the form of convenience when buying, information from friends and family and product attributes as needed.